2010
DOI: 10.1179/174328910x12691245470310
|View full text |Cite
|
Sign up to set email alerts
|

One- and two-component micro powder injection moulding derived from thermoplastic microreplication

Abstract: Today, microinjection moulding represents an established special variant among the different replication techniques strongly promoted by the growing market demand for microcomponents. Spearheading progress towards more sophisticated technologies, micro powder injection moulding offers a large scale fabrication process for metal/ceramic microparts. Minimal details in the range of 10 mm and replication accuracy down to ¡0?3% (in special cases, ¡0?1%) can be reached. With a twofold aim of reducing mounting costs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…This is shown in correlation to the category of micro-component produced, according to the definition used in Section 1.1. [3,40,41]. A recent study suggested that with thorough process optimisation accuracies of ±0.1% of the nominal dimension of some ceramic components could be reached in certain directions of the final part [17,41].…”
Section: Mouldable Dimensions and Achievable Aspect Ratiosmentioning
confidence: 99%
See 2 more Smart Citations
“…This is shown in correlation to the category of micro-component produced, according to the definition used in Section 1.1. [3,40,41]. A recent study suggested that with thorough process optimisation accuracies of ±0.1% of the nominal dimension of some ceramic components could be reached in certain directions of the final part [17,41].…”
Section: Mouldable Dimensions and Achievable Aspect Ratiosmentioning
confidence: 99%
“…Gear structures are sometimes classified as micro-precision components, since they require accurate alignment with other gears or components. Very little is available in the literature about achievable dimensional tolerances by μPIM, but typical reported tolerances are between ±0.2% and ±0.5% of nominal dimensions [3,40,41]. A recent study suggested that with thorough process optimization accuracies of ±0.1% of the nominal dimension of some ceramic components could be reached in certain directions of the final part [17,41].…”
Section: Mouldable Dimensions and Achievable Aspect Ratiosmentioning
confidence: 99%
See 1 more Smart Citation
“…The idea was to co-sinter two components made of different materials in order to achieve the clearance required to facilitate motion by difference in volumetric shrinkage of the two materials. Demonstrations have been made by Piotter et al (2010a and2010b) and Ruh et al (2008 and using powder injection moulding. Such a procedure requires careful adjustment of process conditions to achieve the exact shrinkage in subcomponents, such that a movable clearance is achieved.…”
mentioning
confidence: 99%